Salvia divinorum: a case report - Gürlek, Feridun; Taşdemir, Eyyüp; Teker, Tufan (Journal of Dependence, 2017)
Nowadays, narcotic and enjoyable substances threaten especially adolescents and young people. These substances are fairly common and various. This makes them easier to access. Their use is also closely associated with low socio-economic and socio-cultural conditions. It has been known psychoactive and hallucinogenic effects of Salvia divinorum for many years. It is abused for this purpose. In this study, we presented a patient who developed renal failure and rhabdomyolysis due to immobility after abuse of Salvia divinorum. It has been known that the patient remained immobility for four days after using Salvia divinorum and did not use any additional drugs. In this case report, we examined the effects of Salvia divinorum. Of course, we do not think that a single case report can explain clearly the effect potential of Salvia divinorum. Considering that there were only a few studies in the literature on this regard, we believe that this case can contribute to the literature. Furthermore, the psychosocial features of our case support that the risk of drug use may be higher in individuals with lower levels of income. It has been discussed accompanied to the literature thatthe duration ofaction ofSalvia divinorum used at high doses may be longer than usual and substance dependence is associated with low socio-economic status.